Sociodemographic characteristics are associated with prevalence of high-risk waist circumference and high-risk waist-to-height ratio in U.S. adolescents - Felicia J. Setiono; Laura A. Guerra; Cindy Leung; Tashara M. Leak (BMC, 2021)
Abstract Background Adiposity status in adolescence is associated with various health outcomes in adulthood. Waist circumference [WC] and waist-to-height ratio [WHtR] are measures of abdominal obesity and have shown to be valid predictors of future chronic diseases. However, the relationship between sociodemographic characteristics and WC, as well as WHtR in U.S. adolescents remain unclear. Thus, the study aims to examine associations between sociodemographic characteristics and abdominal obesity among a nationally representative sample of U.S. adolescents. Methods The sample included 4712 adolescents (12-19 years) in the 2007-2016 National Health and Nutrition Examination Survey. Associations between sociodemographic characteristics and abdominal obesity (WC and WHtR) were examined using multiple logistic regression models, adjusted for age, physical activity level, and sedentary activity. Results Around 18% of adolescents had high-risk WC (≥90th percentile) and 34% had high-risk WHtR (≥0.5). Females had higher odds of high-risk WHtR compared to males (OR = 1.46, 95%CI = 1.23-1.72). Mexican American adolescents had higher odds of high-risk WHtR compared to non-Hispanic White (OR = 1.66, 95%CI = 1.24-2.20), non-Hispanic Black (OR = 1.73, 95%CI = 1.26-2.36), and other race/multi-racial adolescents (OR = 1.84, 95%CI = 1.21-2.80). When their parent were college graduates, adolescents had lower odds for high-risk WC compared to when the parent had some college education (OR = 0.68, 95%CI = 0.49-0.93) or a high school degree or less (OR = 0.70, 95%CI = 0.51-0.97). Similar associations were seen between parental education level and high-risk WHtR, as well as between household income and high-risk WHtR. Conclusions Measures of abdominal obesity should be considered to assess burden of adiposity, especially among female adolescents, adolescents from racial/ethnic minority and low socioeconomic status backgrounds. Additionally, future health interventions should consider including changes in WC and WHtR to measure the impact of these interventions.